Latent autoimmune diabetes in adults (LADA) in Asian and European populations. Issue 5 (16th March 2017) - Kumar, Alok; de Leiva, Alberto
Summary: Diabetes mellitus is a chronic disorder caused by relative or absolute insulin deficiency and characterized by chronic hyperglycaemia. It is expected that by year 2025, 80% of all type 2 diabetic patients will be living in developing or low‐ and middle‐income countries. Among Asians, there has been an overall increase in abdominal obesity; however, the risk of diabetes in these populations starts at much lower body mass index as compared to Caucasians. A significant proportion of diabetic patients with adult‐onset, initially nonrequiring insulin treatment, have diabetes‐associated autoantibodies in their sera. A new subclass of diabetes with the designation of latent autoimmune diabetes of adult‐onset (LADA) has been proposed for this category of subjects. Studies have demonstrated that patients with autoimmune diabetes, characterized by the presence of glutamic decarboxylase autoantibodies display a different clinical phenotype from classical type 2 diabetes without glutamic decarboxylase autoantibodies. This subset of phenotypic type 2 diabetes subjects with islet autoantibodies tend to have sulphonylurea failure and need insulin treatment earlier in the disease process. Diagnosing LADA at an initial stage will be important so that insulin can be initiated earlier, facilitating improved glycemic control sooner as well as the preservation of residual beta‐cell function in adult‐onset autoimmune diabetes. Because of differences in dietary habits, environmental factors, and phenotypic characteristics between European and Asian populations, there may be heterogeneity in the prevalence and other characteristics of LADA in these two populations.